PORTFOLIO ASSESSMENT: BENEFITS FOR STUDENTS AT DIFFERENT WRITING PROFICIENCY LEVEL - Listiana, Ineng; Yusuf, Fazri Nur; Isman, Suci Madiarti (Jurnal Pendidikan Bahasa dan Sastra, 2020)
This research discusses the effects of portfolio assessment on students’ improvement in English writing which are related to their writing proficiency levels, the problems encountered by them in each writing proficiency level, and the solution can be implemented regarding the problems found in the research. The research’s subject was Grade VIII which consisted of two classes. The method applied was qualitative method by using test, documentation, and observation  instruments to gather the data. All the scores of the tests are arranged in tables based on Wang and Liao’s criteria (2008) and are presented in bar chart. The results show that every level of writing proficiency has different percentage of improvement, and the low level students have the least improvement; they produced less sentences. The research also found that every level of writing proficiency had problems which were mainly in content, organization, conventions, and vocabulary, while the low level proficiency had another problem in gaining confidence to produce sentences. Beside that, the students did better in using present tense than past tense, and to improve their writing, it was proven that detailed correction and feedback were effective for the improvement.Thus, it is suggested that teacher should give different portion of attention related to correction and feedback, and the most portion should be given to the low level students of writing proficiency as they have the least improvement. Teacher should also give detailed correction and feedback as well to students to make better improvement. The research suggests that portfolio assessment program can be carried out integratedly in English lesson in every semester for all grades of Junior High School since it was proven good for students’ writing improvement.